Scour and Erosion 2016
DOI: 10.1201/9781315375045-58
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of backward erosion piping in heterogeneous sands

Abstract: Backward erosion piping is a relevant failure mechanism for water-retaining structures that determines uncertainty in residual flooding hazard and risk mapping. The occurrence of piping can be predicted using the Sellmeijer model, which is developed and validated for homogeneous granular layers. However, the subsurface encountered below levees can be far from homogeneous. Previous laboratory tests indicated a substantial increase of piping resistance in sand samples with variation of properties in the path of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…For design, it is highly desirable to use 2D models (cross section of the embankment). Progression of the pipe parallel to the barrier, results in an effectively 2D flow field inside the barrier (Negrinelli et al, 2016;Rosenbrand et al, 2018), therefore 2D models are used to analyse the medium-scale tests.…”
Section: Modelling the Medium-scale Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For design, it is highly desirable to use 2D models (cross section of the embankment). Progression of the pipe parallel to the barrier, results in an effectively 2D flow field inside the barrier (Negrinelli et al, 2016;Rosenbrand et al, 2018), therefore 2D models are used to analyse the medium-scale tests.…”
Section: Modelling the Medium-scale Experimentsmentioning
confidence: 99%
“…Therefore, a pipe which encounters the barrier is prevented from progressing upstream and will rather grow parallel to the barrier in the background sand, seeking the weakest path (Figure 1). This has the added benefit that it reduces the concentration of flow in the barrier, further reducing the hydraulic gradient in the barrier (Negrinelli et al, 2016;Rosenbrand et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has led to the development of finite element (FE) models for simulation of BEP in uniform soils (e.g., Sellmeijer 2006;van Esch et al 2013;Rotunno et al 2017;Robbins and Griffiths 2018a). Meanwhile, laboratory experiments have demonstrated that BEP is highly sensitive to soil heterogeneities (Negrinelli et al 2016) with BEP becoming less likely as soil variability increases. As such, models assuming homogenous soil profiles (1) may be overly conservative and (2) may not capture the process sufficiently to yield reliable probabilities of failure.…”
Section: Introductionmentioning
confidence: 99%